Verification of the reactivity of immunoglobulins in dried blood spots collected for onchocerciasis sero-surveillance by an Escherichia coli ELISA - Hassan, Hassan K.; Miley, Kristi M.; Unnasch, Thomas R. (Frontiers in Tropical Diseases, 2024)
The World Health Organization guidelines for verification of onchocerciasis elimination include demonstrating that the prevalence of exposure to the parasite in individuals born since transmission was interrupted needs to be less than 0.1%. The guidelines recommend using seropositivity to an Onchocerca volvulus specific antigen (Ov16) for this purpose. Ov16 seropositivity has most often been assessed using the Ov16 ELISA assay. Currently, the Ov16 ELISA assay includes internal positive and negative controls to monitor for proper assay performance but does not control for the quality of the dried blood spots (DBS) being tested. Previous studies have reported a high prevalence of antibodies recognizing Escherichia coli in children. Through the development of an ELISA assay to detect antibodies recognizing E. coli, a common commensal in humans, DBS may be prescreened for quality assurance prior to testing for Ov16. Results demonstrated antibodies to E. coli were detected in 100% of randomly selected serum samples collected from O. volvulus infected individuals residing in an onchocerciasis hyperendemic area. Furthermore, when DBS were improperly stored, the E. coli antibodies were found to decay over a period of one week, while remaining unchanged over the same period in properly stored samples. Similarly, E. coli antibodies were detected in 100% of a batch of field collected properly stored DBS, while being present only in 5% of a batch of improperly stored spots. This study demonstrates the value of E. coli ELISA for DBS quality control testing and validation of proper storage of collections of DBS for the Ov16 ELISA.